Ogilvie's syndrome after an emergency caesarean section: A case report - Ankita Bhakta; Tingmin Li; Gauthami Bhagwanani; Tanushree Rao (Elsevier, 2022)
Ogilvie's syndrome, or acute colonic pseudo-obstruction, is a rare presentation occasionally observed postpartum, particularly following caesarean sections. Challenges in diagnosis often lead to delays in initiation of treatment, which significantly increases complications, including caecal ischaemia, perforation, sepsis and death. This case report describes the development of Ogilvie's syndrome within 24 h of an emergency caesarean section which was promptly recognised and confirmed by computed tomography, which demonstrated caecal dilatation of 9.7 cm without evidence of mechanical obstruction. An elevated level of C-reactive protein of 320 mg/L raised early clinical suspicion of caecal ischaemia, and this was managed endoscopically. Fortunately, the patient did not have any significant complications despite the high morbidity and mortality rate associated with Ogilvie's syndrome, highlighting the importance of clinician awareness and early initiation of management.